T-cell and plasma cell populations in coeliac small intestinal mucosa in relation to dermatitis herpetiformis. Issue 7 (July 1989) - Jenkins, D; Goodall, A; Scott, B
Abstract : Differential lymphocyte and plasma cell counts and measurements of mucosal architecture were studied in small intestinal biopsies from 17 controls and 17 patients with untreated uncomplicated coeliac disease of whom five also had dermatitis herpetiformis. Intraepithelial T-cell and plasma cell counts and measurements of mucosal architecture were not significantly different in the two coeliac groups but both groups differed from the controls. Lamina propria T-cell counts were significantly higher in the patients who also had dermatitis herpetiformis than in uncomplicated coeliac disease, with a significant increase in the Leu 2 (CD8) positive (cytotoxic/suppressor) T-cell subset. This suggests a specific abnormality of T-cell control of immune responsiveness in the pathogenesis of the skin manifestations of dermatitis herpetiformis which is not found in uncomplicated coeliac disease.